2017
DOI: 10.1097/md.0000000000008954
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Burkitt lymphoma

Abstract: Rationale:Burkitt lymphoma (BL) is an endemic tumor in Africa but rare sporadic cases are diagnosed in Europe.Patient concerns:A 60-year-old woman was hospitalized with fulminant hematemesis and a history of recurring melena.Diagnoses:The upper gastrointestinal endoscopy revealed a tumor of the antrum.Interventions:Emergency gastrectomy was performed.Outcomes:Gross findings revealed an ulcerated tumor with elevated margins and several perigastric and extragastric lymph nodes. Histological examination showed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Clinically, symptoms include abdominal pain, diarrhea, anemia, or gastrointestinal bleeding [3] . Indeed, Gurzu et al [ 4 ] in their case report, a gastric lymphoma was found after performing a gastroscopy to a patient that consulted for melenas. Imaging modalities play a crucial role in correct diagnosis and therefore contribute to treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, symptoms include abdominal pain, diarrhea, anemia, or gastrointestinal bleeding [3] . Indeed, Gurzu et al [ 4 ] in their case report, a gastric lymphoma was found after performing a gastroscopy to a patient that consulted for melenas. Imaging modalities play a crucial role in correct diagnosis and therefore contribute to treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis, patients have high tumor burden from bulky disease and have elevated lactate dehydrogenase levels, with high uric acid levels. Cases regarding atypical presentations such as BL mimicking Cronh's disease, origin from the nasal septum, gingival involvement, Kruckenberg tumor by ovarian infiltration with spread to stomach and presentation with peritoneal carcinomatosis has been described in the literature [5][6][7]. ).…”
Section: Immunodeficiency Associated Blmentioning
confidence: 99%
“…Sporadic Burkitt's lymphoma, most presenting as leukemia, one-third of cases had chromosomal breakpoints in the joining region of IgH [5]. Criteria for diagnosis BL include immunohistochemical stains CD 20 (+), CD10 (+), BCL-6 (+), and BCL-2 (− )and a proliferative fraction> 95% as per WHO classification[6].…”
mentioning
confidence: 99%
“…The most common site of the involvement for sporadic BL is the abdomen with the most frequently involved partsmall bowel at the ileocecal region (due to the high concentration of lymphoid tissue) and mesenteric and retroperitoneal lymph nodes (commonly presented as abdominal and pelvic masses) (Kalisz et al, 2019). A review of the literature reveals separate single case reports where other rare primary localisations of BL are described: extra-nodal structures of the abdomen (stomach, colon and rectum, liver, spleen, kidneys, adrenal glands, pancreas, testis, ovaries, peritoneum), thoracic region (mediastinal or hilar lymph nodes, pericardium and myocardium, lung parenchyma and endobronchial involvement, pleura and breast), extra-nodal structures of the head and neck (palatine, lingual tonsils, and adenoids of the nasopharynx), skin, thyroid gland, central nervous system and bone marrow (the last two are most common in a recurrent or treatment-resistant disease) (Modi et al, 2015;Gurzu et al, 2017;Kalisz et al, 2019;Malik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%